INTEGRASI PEMBELAJARAN BAHASA INGGRIS BERBASIS PENDEKATAN ISLAMI - YOVITA DYAH PERMATASARI (JURNAL PENDIDIKAN GLASSER, 2019)
This research discussed about the use of Teaching English with Islamic Values. The lecture teached the students’ by using Islamic culture involved in the way of teaching English. This research conducted in Islamic Institution of Al- Falah Assunniyyah Kencong. It included of students in  Islamic department of education. By using interview, observation and also the score of students’ in English subject. The researcher analyze that this research take many advantages for the students and also the lectures. They very interesting in the process of study English without ignore the Islamic culture. And also enjoy the class with  implemented the values of Islamic culture in their daily life. The findings of this study indicate that lecturers have taught English in islamic contexts. But the teaching provided is only in a simple scope, besides that the lecturer still does not have a reference to teaching materials that are in accordance with the study program / department of the students being taught. the application of ESP (English for Specific Purposes) needs to be developed ,in order to get  the synergy between teaching materials for courses with study programs / student majors can be allied and balanced